Computing in Civil Engineering 2015 2015
DOI: 10.1061/9780784479247.084
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of BIM Integration with Facilities Management: A Preliminary Case Study

Abstract: There is an increasing recognition that, to maximize the benefits of Building Information Modeling (BIM), it should be deployed in such a way that it remains useful beyond the design and construction phase of projects. This means that it should be utilized in the facilities management phase of a constructed facility. This paper focuses on the identification of benefits gained from the effective integration of BIM in Facilities Management. Drawing on literature from previous research, it argues for the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Some researchers (Dias and Ergan 2016;Liu and Issa 2016;Sattenini et al 2011;Terreno et al 2015;Thabet et al 2016) have attempted to determine LOD needed for O&M phase by interviewing experts. Liu and Issa (2016) conducted a survey questionnaire to define a list of maintenance problems such as Lack of equipment accessibility, poor design of equipment layout, lack of adequate space for mechanical room, lack of space designed in the ceiling to contain MEP systems, limited space for AHU filter access that ought to be deliberated in design phase.…”
Section: Lod For Fmsmentioning
confidence: 99%
“…Some researchers (Dias and Ergan 2016;Liu and Issa 2016;Sattenini et al 2011;Terreno et al 2015;Thabet et al 2016) have attempted to determine LOD needed for O&M phase by interviewing experts. Liu and Issa (2016) conducted a survey questionnaire to define a list of maintenance problems such as Lack of equipment accessibility, poor design of equipment layout, lack of adequate space for mechanical room, lack of space designed in the ceiling to contain MEP systems, limited space for AHU filter access that ought to be deliberated in design phase.…”
Section: Lod For Fmsmentioning
confidence: 99%
“…Despite numerous benefits reported, past research [27] [28] [29] found BIM applications in FM still at the initial and emerging stages and encouraged further research to address the existing implementation challenges. Challenges found in these research efforts for incorporation of BIM in FM can be summarized as: absence of structured method for incorporating BIM in FM processes; lack of proper tools for demonstrating BIM benefits to FM; limited knowledge on types of information to be collected and methods and tools to be used for applying BIM in FM; too much detailed specifications required for BIM development; lack of expertise for working with BIM in public organizations; resistance to change previously adopted methods; and challenges for linking BIM to the current tools used in FM.…”
Section: -Use Of Bim In Fm Processesmentioning
confidence: 99%
“…In addition, some studies have discovered that the benefits of BIM are in improvement of design quality, information sharing ability, reduction in construction and design errors, faster working environment, enhancing efficiency, operational efficiency, and so numerous (Doumbouya, Gao et al 2016). With abundant benefits, BIM utilization and its possible benefits can be divided into five categories: 1) life cycle cost control; 2) effective construction process; 3) design and quality improvement; 4) decision-making support; and 5) risk management, and some are more abundant in specific cases, such as facilities management (Tomek and Matějka 2014, Terreno, Anumba et al 2015, Enshassi, Hamra et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If we think about the benefits of BIM utilization, however, then some financial benefits and associated advantages should be elaborated. There are studies describing benefits in risk management, construction time reduction, error management, and some other issues that may involve costs (Love, Matthews et al 2014, Terreno, Anumba et al 2015, Dakhil, Underwood et al 2016. But in many cases, precise measurements on financial costs of BIM utilization can be hardly accessible.…”
Section: Introductionmentioning
confidence: 99%